Implikasi Hukum terhadap Keamanan Lender dalam Kasus Penipuan pada Platform Fintech P2P Lending di Indonesia - Putu Amanda Githa Kayla PR. (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of information technology has presented new legal challenges, particularly regarding the protection of personal data and information security. This research aims to examine the urgency of establishing legal regulations that are adaptive to the dynamics of information technology in Indonesia, and to examine the extent to which existing regulations are able to accommodate the needs of legal protection in the digital ecosystem. The research method used is normative juridical with a statutory approach and conceptual analysis of the applicable legal framework. The findings show that existing regulations, such as the Electronic Information and Transaction Law and the Personal Data Protection Law, still face obstacles in implementation, including overlapping rules, weaknesses in law enforcement, and low public digital literacy. The implications of this research emphasize the importance of continuous legal reform, synergy between law enforcement agencies, and increased public awareness to create a safe and equitable digital ecosystem.